2002
DOI: 10.1016/s0886-3350(02)01366-4
|View full text |Cite
|
Sign up to set email alerts
|

Corneal optical coherence tomography before and after phototherapeutic keratectomy for recurrent epithelial erosions

Abstract: Using noncontact corneal OCT, corneal and epithelial thickness changes and the wound-healing response in the anterior corneal stroma could be evaluated after PTK in patients with recurrent epithelial erosions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 27 publications
0
25
0
2
Order By: Relevance
“…Although specific anterior segment OCT devices with particular refinements for corneal imaging have been developed, we used a retinal OCT system to analyze CCIs in detail. Although several authors have found this system useful in assessing and monitoring corneal conditions in vivo, 12,[14][15][16][17][18][45][46][47][48] we found the images difficult to interpret. The incision angles measured in our study were generally overestimated for two reasons.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Although specific anterior segment OCT devices with particular refinements for corneal imaging have been developed, we used a retinal OCT system to analyze CCIs in detail. Although several authors have found this system useful in assessing and monitoring corneal conditions in vivo, 12,[14][15][16][17][18][45][46][47][48] we found the images difficult to interpret. The incision angles measured in our study were generally overestimated for two reasons.…”
Section: Discussionmentioning
confidence: 76%
“…11 Although the technology has been used primarily to diagnose optic nerve and retinal pathology, it is also valuable in the study of the cornea. [12][13][14][15][16][17][18] Regarding this point, McDonnell et al 9 found that CCIs did not have a stable wound morphology in an artificial experimental model using cadaver and rabbit eyes because intraocular pressure (IOP) variations resulted in movement of the wound edges. Their results suggest that transient gaping of the incision allows bacteria to reach the aqueous, supporting the possibility that CCIs are responsible for an increased incidence of postoperative endophthalmitis.…”
mentioning
confidence: 99%
“…This could be related to the decrease in discrimination for internal corneal structures, but is also influenced by the measurement range available for statistical analysis [2]. Furthermore, the outer OCT signal is not specific for the epithelium, partly consisting of a surface-related signal [30,32]. In the patients with swollen corneas and compensatory Descemet's folds at the posterior side due to pseudophakic bullous keratopathy examined in this study, great variations in thickness values could be another source of variability.…”
Section: Discussionmentioning
confidence: 87%
“…However, these specular reflections can lead to loss of important signal features at higher saturation levels, and thus, mask reflections from deeper cellular and connective tissue layers of the cornea. Although overall changes in the corneal thickness and marked pathological changes were easily determined by OCT, the precise location of intracorneal tissue boundaries and fine adjacent substructures in corneal OCT images is more difficult to define [30,32]. This is also dependent on the relatively small and heterogeneous intracorneal fluctuations in the layer-to-layer refractive index and scatter coefficients with possible complete, partial, or multiple backscatter of light.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation